Zero [videorecording (DVD)] - Herbulot, Jean Luc; Miller, Hus; Miller, Hus; McHarg, Cam; Dourdan, Gary (Well Go USA Entertainment, 2025)
Two strangers searching for purpose in Dakar, Senegal, wake up with bombs strapped to their chests, counting down from ten hours. Controlled by a mysterious voice, they must complete a series of chaotic missions with devastating consequences. As the city erupts in protest against Western influence, the reluctant partners race for redemption. ZER0 is a thrilling, darkly humorous tale of survival, connection, and the human search for meaning.